Assessment of in vitro biological properties of aqueous extracts of Murraya koenigii (L.) Spreng, Thymus vulgaris L., and Ocimum gratissimum L. leaves - Oso, Babatunde Joseph (Array, 2020)
This study investigated the in vitro biological properties of aqueous extracts of dried leaves of Murraya koenigii, Thymus vulgaris, and Ocimum gratissimum. The phenolic and flavonoid contents were evaluated colorimetrically. The antioxidant capacities were assessed through scavenging of 1,1-diphenyl-2-picrylhydrazyl (DPPH•), 2,2’-azinobis (3-ethylobenzothiazoline-6-sulphonate) radical (ABTS+) and nitric oxide (NO); the reducing potentials and total antioxidant capacities were also estimated. The anti-inflammatory potentials were investigated through the inhibitions of lipoxygenase activity, albumin denaturation, and proteinase activity. The inhibitory actions against α-amylase, α-glucosidase, sucrase and albumin glycation were also evaluated. The extracts contained significant amounts of phenolic compounds with the extract of T. vulgaris having the highest concentrations of phenolics and flavonoids; correspondingly, the extract of T. vulgaris had the lowest IC50 values for DPPH•, ABTS+, and NO scavenging. The extract of T. vulgaris significantly inhibited (p<0.05) lipoxygenase activity, albumin denaturation and proteinase activity similar to indomethacin. The actions of the extracts against carbohydrate digesting enzymes and the formation of protein modification varied significantly (p<0.05). This study provides insight into the functional and medicnial properties of M. koenigii, T. vulgaris, and O. Gratissimum.